The Structure of Human Resources for Science and Technology in EU Countries - Pleśniarska, Aleksandra (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The main aim of the article is to analyse the structure of Human Resources for Science and Technology (HRST), Core of Human Resources in Science and Technology (HRSTC) by age group, and the annual average growth rate of HRST in the EU member states. The article examines the effectiveness of human resources by looking at patent applications to the EPO and the number of the most cited scientific publications.